Does Working Memory Mediate the Link Between Dispositional Optimism and Depressive Symptoms?. Issue 6 (21st September 2016) - Alloway, Tracy Packiam; Horton, John C.
Summary: The aim of this study was to explore the interplay between working memory (WM), dispositional optimism, and depressive symptoms in participants across a wide age band (16–79 years) in a nonclinical sample using a computer‐based interface. We administered tests of visuospatial WM (processing and recall), dispositional optimism (optimism and pessimism), and self‐reported depression. There were two main findings: 1) both optimism and pessimism were independent predictors of a self‐rated depression score; 2) WM recall scores predicted both optimism and pessimism. The findings suggest the following pattern: according to the negativity bias, a pessimistic outlook presents as a strong stimulus for attentional allocation, which results in depression. However, a strong WM can counter this pattern, as individuals can allocate attention to the weaker stimulus, which is an optimistic outlook. Copyright © 2016 John Wiley & Sons, Ltd.